Hubungan Tingkat Pengetahuan Ibu Post Partum dengan Baby Blues Syndrom berdasarkan Tingat Kecemasan di Rumah Sakit Marinir Cilandak Tahun 2022 - Nurcahya, Bunga (Journal of Nursing Education and Practice, 2024)
Introduction: Baby Blues is a mild effect disorder syndrome that often appears in the first week after delivery peaks on the third to fifth day and attacks within 14 days after delivery. The causes of Baby Blues Syndrome according to Marmi (2012), namely hormonal changes, stress, breast milk not coming out, frustration, fatigue, lack of support from husband and family, fear of losing the baby, and boredom. Objectives: To find out the relationship between the level of knowledge of postpartum mothers and baby blues syndrome based on the level of anxiety at the Cilandak Marine Hospital in 2022. Method: This research is quantitative correlational research using a "cross-sectional approach". The independent variable is the level of knowledge, and the dependent variable is the level of anxiety. The sample for this research was 30 people taken as a total sampling. The research instrument uses a questionnaire. The collected data was then tested using the chi-square analysis test. Result: The results of the Chi-square test with probability obtained a p-value of 0.036 (p-value <0.05). Then H0 is rejected, and Ha is accepted. Conclusion: There is a relationship between the level of knowledge and the level of anxiety of the mother with baby blues syndrome.